The Influence of Indomaret Sales Promotion on Instagram on Purchasing Decisions (Survey of Followers of the @Indomaret Instagram Account) - Khoiriqadafi, Mohammad; Purnamasari, Oktaviana (PT FORMOSA CENDEKIA GLOBAL, 2023)
In this era of globalization, modern urban society is now spoiled by the presence of various shopping centers. Sometimes the location is even within one area. The purpose of this research is to find out how much influence sales promotion on @Indomaret Instagram has on purchasing decisions, consumers on followers of the @Indomaret Instagram account. The theories used are marketing communications, sales promotion, and purchasing decisions. The approach to this research is quantitative with a survey method, data collection technique by distributing questionnaires to 70 respondents following the @indomaret Instagram account. The study utilized a straightforward random sampling method for sampling. The research outcomes indicate a connection between the sales promotion on Instagram @Indomaret and the purchasing choices made by consumers. The coefficient of determination data shows that the sales promotion factor has an influence of 45.6% on purchasing decisions, while the remaining 54.4% is influenced by factors other than the factors studied